A salutary biotechnical approach for explosive identification and border patrol using electrophysiological signals - Santhanakrishnan, C; Peermeer Labbai, T; S. Dudala, Shailesh; Sai Santhosh Nag, Y (International Journal of Engineering and Technology, 2018)
This paper visualizes a salutary approach to maneuver and implement a successful sensor embedded rover that could be used for the surveillance of harmful components like bombs and underground mines that usually contain embedded metallic shrapnel and avoid detonation owning to its light frame. In case of any hostile situation, rescue operations are performed by human and trained dogs in a very precarious pandemonium risking the chances of victimizing themselves. Therefore, to enhance the safety and celerity1 of any defensive op, the rover is controlled directly through bio-electrical signals which are spontaneous in decision making, tweaking their application by using the variations in Electroencephalographic (EEG) and Electrooculographic (EOG) readings in the blink of an eye. Subsequently, the raw mindwave-sensor data is imported into MATLAB, thru the NeuroSky Headset RF receiver, these values are interpreted to normalized ranges so that 4 directions or degrees of freedom shall be implemented, thus opening up possibilities of handsfree-operation. The rover includes Passive-Infrared sensors (PIR) which are used for detecting human presence, motion/mobility and for detecting the illegal entry of intruders across any defensive line. The ATMega 328P microcontroller onboard the Arduino is used to control the sensors on board the while the ZigBee modules are used for ultra-low voltage transmitting and receiving sensor data. Furthermore, an ultrasonic sensor to analyze terrain and measure the distance from impending intrusions vastly improves the rover’s mobility on challenging terrains.